If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1) + y = 2 Multiply 2 * -1 -2 + y = 2 Solving -2 + y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = 2 + 2 Combine like terms: -2 + 2 = 0 0 + y = 2 + 2 y = 2 + 2 Combine like terms: 2 + 2 = 4 y = 4 Simplifying y = 4
| 4x^2+20x+25=81 | | x^2+21x-1024=0 | | 80-9/2x=0 | | 3(-1)-y=-7 | | 80-9/2x=0 | | x-8.6=-6.7 | | 2x^2-56=0 | | 10/25 | | t+28=21 | | 2h+3s=145 | | (-y^2-3y-5)-(-3y-7y+4)= | | -5(9)-5y=-50 | | c+9=3 | | 3/7+2/5 | | x^2-18x=7 | | 4x+15=5x+12 | | 27-5x=x+13 | | (7x-6y)+(3x+3y-3)= | | -9-5y=-50 | | 6a-5-4a=2 | | 5+5=010 | | 9t+8t+3t-16t=32 | | -25x+38x+26x+3x-41x+25=35 | | -5x-5(3x-26)=-50 | | -27d-d+22d+9=-45 | | .5x^2+1.5x=4 | | 9p-24p=30 | | -12m-19=77 | | 12b-3b-b+19b-17=10 | | 5(1.093x+1)=6 | | h-h+3h+3h+4h-9=11 | | x^2/2+3x/2=4 |